THE INFLUENCE OF PERCEIVED VALUE AND ELECTRONIC WORD OF MOUTH (E-WOM) ON GEN-Z INTENTION TO USE SHOPEE IN MANADO - Santoso, Cecilia Glory; Worang, Frederik Gerard; Tielung, Maria Veronika J (Universitas Sam Ratulangi, 2024)
The convenience that comes along with e-commerce services attracts a lot of consumers to use the application. The purpose of this study is to find out the influence of perceived value and electronic word of mouth (e-WOM) on Gen-Z intention to use Shopee in Manado. This study is approached by a quantitative method. The data collection was carried out through a questionnaire with purposive sampling technique that are distributed to 100 respondents of Gen-Z. The data is analyzed using Multiple Linear Regression. Based on the result, it is found that perceived value partially influence intention to use. Then, electronic word of mouth (e-WOM) also partially influence intention to use. Lastly, perceived value and electronic word of mouth (e-WOM) simultaneously influence intention to use. These findings indicate that when Gen-Z perceived a good value of the service, it can formulate an intention to use the service. Also, online information that are being shared on the internet about a service, plays a crucial role in creating the intention of Gen-Z to use a service. Keywords: Perceived Value, Electronic Word of Mouth (e-WOM), Intention to Use